The discursive construction of hydraulic fracturing in South Africa : a critical analysis of media texts from 2011 to 2012 - Smit, Simone Nicole (Stellenbosch : Stellenbosch University, 2014)
Thesis (MA)--Stellenbosch University, 2014.